Time efficient secure DNA based access control model for cloud computing environment - Namasudra, Suyel; Roy, Pinki; Vijayakumar, Pandi; Audithan, Sivaraman; Balusamy, Balamurugan (Future generation computer systems, 2017)
The uses of Big Data (BD) are gradually increasing in many new emerging applications, such as Facebook, eBay, Snapdeal, etc. BD is a term, which is used for describing a large volume of data. The data security is always a big concern of BD. Besides the data security, other issues of BD are data storage, high data accessing time, high data searching time, high system overhead, server demand, etc. In this paper, a new access control model has been proposed for BD to solve all these issues, where fast accessing of the large volume of data are provided based on the data size Here, a long 512-bit Deoxyribonucleic Acid (DNA) based key sequence has been used for improving the data security, and it is secured against the collision attack, man-in-the-middle attack, internal attack, etc. The proposed scheme is evaluated in terms of both theoretical and experimental results, which show the proficiency of the proposed scheme over the existing schemes. •The proposed scheme uses data sizes for efficient and secure data accessing.•To improve the data security, a long 512-bit key has been used in the proposed scheme.•Key generation and key retrieval time at the data owner’s side and user’s side are respectively less.•Experimental results and theoretical discussions prove the efficiency of the proposed scheme.